Cemento-Ossifying Fibroma in the Mandibular Posterior Region: 2 Case Reports - Duran, Merve Hacer; Türkcan, Mehmet Buğra; Baybars, Sümeyye Coşgun; Öçal, Mustafa Çağdaş (Biruni Üniversitesi, 2024)
Aim Cemento-ossifying fibroma (COF) is a mesenchymal, benign odontogenic tumor of the jaws that originates from the mesenchymal blast cells of periodontal ligament and can form osteoid, bone, cement-like tissue, fibrous cellular tissue or a combination of them. In this case report, it is aimed to present clinical, radiological and histopathological examination of two cemento-ossifying fibroma cases. Case Report A 36-year-old systemically healthy female patient was referred to our faculty due to a lesion detected in the right mandibular posterior region. As a result of the clinical and radiological examination, an asymptomatic tumoral structure with a mixed appearance and regular borders was detected. No expansion was detected in the right mandibular posterior region. The patient was referred to the Department of Oral and Maxillofacial Surgery for biopsy. According to the biopsy report, it was learned that this tumoral structure was a COF. A 38-year-old systemically healthy female patient was admitted to our faculty due to gingival bleeding. As a result of the clinical and radiological examination, an asymptomatic lesion with a radiolucent appearance and sclerotic borders was detected in the right mandibular posterior region. According to the patient’s biopsy report, it was discovered that this lesion was a COF. Discussion COF may exhibit different clinical and radiological behaviors based on its stage. Diagnosis and treatment planning of COF should be made with clinical, radiological and histopathological examination. Conclusion Two COF cases are reported with their detailed clinical and radiological examinations in this paper.
Keywords: Oral and Maxillofacial Radiology; Ağız; Diş ve Çene Radyolojisi